Edukasi Streching Cervical pada Kasus Neck Pain di SMA 5 Merangin - Wanti Hasmar; Putra Hadi (Jurnal Abdimas Kesehatan (JAK), 2022)
The use of smartphones or communication tools that can be easily connected to the internet has increased from time to time. Neck Pain that occurs in students can affect various aspects of life, such as reduced work productivity, disrupted quality of life, and school activities. Community service activities were carried out in March-April 2021 with discussion methods and presenting materials and illustrated posters related to cervical stretching education in Neck Pain cases through Zoom Meetings. In this illustrated poster there are 4 cervical stretching movements. This Community Service (PKM) aims to be used as a source of knowledge and management of neck pain and neck stiffness due to neck pain in high school students 5 Merangin. The results of the evaluation through questions and answers through the Zoom Meeting application are that on average students know and can practice cervical stretching correctly, and complaints of neck pain and neck stiffness are reduced.